Correction: Tantalum(v) 1, 3-propanediolate β-diketonate solution as a precursor to sol–gel derived, metal oxide thin films. Issue 53 (28th August 2020) - Beale, Christopher; Hamacher, Stefanie; Yakushenko, Alexey; Bensaid, Oumaima; Willbold, Sabine; Beltramo, Guillermo; Möller, Sören; Hartmann, Heinrich; Neumann, Elmar; Mussler, Gregor; Shkurmanov, Alexander; Mayer, Dirk; et al.
Abstract : Correction for 'Tantalum(v ) 1, 3-propanediolate β-diketonate solution as a precursor to sol–gel derived, metal oxide thin films' by Christopher Beale et al., RSC Adv., 2020, 10, 13737–13748, DOI: ; 10.1039/D0RA02558E .